Сhanges in the chemical composition of apple fruit depending on the cultivation in the regions - Hakimov Muqumjon Usmonovich; Mamajonov Gaybullo (International Journal on Orange Technologies, 2021)
The fruits and species of apples are common on all continents of the world, as well as in the hemispheres in the north and south. Apple fruit takes the 4th place in the world among fruit crops. The world produces 61 million tons of apples per year. (FAO, 2019). It is known that the fetus contains various nutrients, sugars, proteins, ascorbic acid and minerals.